2010
DOI: 10.3109/08860220903391234
|View full text |Cite
|
Sign up to set email alerts
|

Food Intake and Nutritional Status in Stable Hemodialysis Patients

Abstract: This is a cross-sectional, multicenter, controlled study aiming to evaluate changes of actual dietary nutrient intake in 94 stable hemodialysis patients in respect to 52 normal subjects and guideline recommendations, and to assess the prevalence of signs of malnutrition. Energy and nutrients intake assessment was obtained by a three-day period food recall. Anthropometric and biochemical parameters of nutrition, bioelectric impedance vector analysis, and subjective global assessment (SGA) have been performed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
5
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 36 publications
5
39
5
2
Order By: Relevance
“…As serum albumin level is a marker of nutritional status, we think that this result suggests an association between nutrition and inflammation in ESRD patients. This result is consistent with the findings of a recent trial studying nutritional status in HD patients (13). Unlike the results of similar studies, we could not find any significant relation between ADMA and BMI (13,19).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…As serum albumin level is a marker of nutritional status, we think that this result suggests an association between nutrition and inflammation in ESRD patients. This result is consistent with the findings of a recent trial studying nutritional status in HD patients (13). Unlike the results of similar studies, we could not find any significant relation between ADMA and BMI (13,19).…”
Section: Discussionsupporting
confidence: 92%
“…This result is consistent with the findings of a recent trial studying nutritional status in HD patients (13). Unlike the results of similar studies, we could not find any significant relation between ADMA and BMI (13,19). This may be due to the small number of patients in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nutritional guidelines suggest daily energy intake higher than 30-35 kcal/kg ideal body weight and daily protein intake higher than 1.1-1.2 g/kg ideal body weight, 6,7 mostly because of the catabolic effect and of the losses of amino acids, peptides, and proteins related to the hemodialysis procedure. Many studies reported that these recommendations are far from being fully obtained; [8][9][10] moreover, chronic renal failure is associated with loss of appetite and reduced food intake, especially when toxins removal by hemodialysis is inadequate. 11 Dialysis adequacy and nutritional counseling are the first attempts to ameliorate nutritional status, and then oral nutritional supplements should be employed including energy and protein sources.…”
Section: Introductionmentioning
confidence: 99%
“…The primary approach to manage hyperphosphatemia in the CKD patient is through oral administration of phosphate binders and dietary phosphate reduction [3,26]. Failure to control the hyperphosphatemic condition in CKD patients significantly increases the risk of cardiovascular disease [27].…”
Section: Discussionmentioning
confidence: 99%